THE ACTUALIZATION OF SEARCH OF SENSE-VITAL VALUES AS A PHILOSOPHICAL-EDUCATIONAL PROBLEM - E. G. Rogova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of this article is determination and revelation of philosophical and educational axiostrategies of actualization of searching the special place of sense-vital values in the process of axio-sphere forming by growing the personality as a representative of the modern technocratic society which takes place in the process of his education. Methodology. In the study of the philosophic and educational constructs of actualization of the searching the sense-vital values the methods of the systematically, socio-cultural and comparative analysis were used, that allowed to define the axiostrategies of subsequent development of meaning and formative education. Scientific novelty of work consists in the philosophical constructs of development by the meaning-formative education in the conditions of the world values-view pluralism which are considered in the determining context of definition of «axiostrategу» notion and also the deep connections and synthesizing values of «the generalizing high level». They are general for most wide-spread (atheistic and religious) varieties of the existential education in the sense-vital aspect. Conclusions. The axiostrategies of searching of the life sense are formulated and exposed as an independent global personality construction which has powerful motivational nature and not only shows the certain level of philosophical culture, but also the internal change of personality brings it on the new degree of life, which is identical in its sense and ultimate aim with the adoption of own human existence. That is instrument in self-actualization, self-realization of personality in accordance with the individual possibilities, interests, aspirations, and also providing the firmness of personality in Postmodern terms and that is the urgent task of modern education, because the actualization of sense-vital problems is one of the main mission of comprehensive school.